2014
DOI: 10.1016/j.abb.2013.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Hypothiocyanous acid oxidation of tubulin cysteines inhibits microtubule polymerization

Abstract: Thiol oxidation is a probable outcome of cellular oxidative stress and is linked to degenerative disease progression. In addition, protein thiol redox reactions are increasingly identified as a mechanism to regulate protein structure and function. We assessed the effect of hypothiocyanous acid on the cytoskeletal protein tubulin. Total cysteine oxidation by hypothiocyanous and hypochlorous acids was monitored by labeling tubulin with 5-iodoacetamidofluorescein and by detecting higher molecular weight inter-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…In the case of tubulin, it has been observed that the assembly and polymerization of this protein depend on redox changes [35][36][37]. For example, in mammalian microtubule [38], cysteine oxidation to disulfides altered the ability of the proteins to promote the assembly of microtubules from tubulin.…”
Section: Identification Of Protein Substrates For Tctxniimentioning
confidence: 99%
“…In the case of tubulin, it has been observed that the assembly and polymerization of this protein depend on redox changes [35][36][37]. For example, in mammalian microtubule [38], cysteine oxidation to disulfides altered the ability of the proteins to promote the assembly of microtubules from tubulin.…”
Section: Identification Of Protein Substrates For Tctxniimentioning
confidence: 99%
“…Indeed, it has been reported that oxidation of tubulin cysteines by peroxynitrite, 2-[(1-methylpropyl)dithio]-1H-imidazole or hypothiocyanous acid inhibits microtubule polymerization [5961]. Since cysteine residues are not part of the protein domains responsible for the dimerization and polymerization of tubulin [62], more studies are needed to determine if this is a direct effect on filament stabilization, or an effect on the binding of proteins that regulate the polymerization process; in addition, more work is needed to determine the endogenous sources of ROS that may mediate these oxidations in vivo.…”
Section: Cytoskeleton and Cytoskeleton-associated Proteins As Targetsmentioning
confidence: 99%
“…57,58 Thus, it seems that apart from mechanisms that perceive cellular redox status, additional regulatory mechanisms sense the redox status of tubulin. Since the later is strongly related to the capability for MT assembly, 59,60 such mechanisms may protect tubulin against irreversible oxidation.…”
Section: Some Aspects On the Oxidation Of Tubulinsmentioning
confidence: 99%